Antibody Responses Against Anopheles darlingi Immunogenic Peptides in Plasmodium Infected Humans - Londono-Renteria, Berlin; Montiel, Jehidys; Calvo, Eric; Tobón-Castaño, Alberto; Valdivia, Hugo O.; Escobedo-Vargas, Karin; Romero, Luz; Bosantes, Maria; Fisher, Michael L.; Conway, Michael J.; Vásquez, Gissella M.; Lenhart, Audrey E. (Frontiers in Cellular and Infection Microbiology, 2020)
Introduction: Malaria is still an important vector-borne disease in the New World tropics. Despite the recent decline in malaria due to Plasmodium falciparum infection in Africa, a rise in Plasmodium infections has been detected in several low malaria transmission areas in Latin America. One of the main obstacles in the battle against malaria is the lack of innovative tools to assess malaria transmission risk, and the behavioral plasticity of one of the main malaria vectors in Latin America, Anopheles darlingi. Methods: We used human IgG antibodies against mosquito salivary gland proteins as a measure of disease risk. Whole salivary gland extract (SGE) from An. darlingi mosquitoes was used as antigen in Western blot experiments, in which a ~65kDa protein was visualized as the main immunogenic band and sent for sequencing by mass spectrometry. Apyrase and peroxidase peptides were designed and used as antigens in an ELISA-based test to measure human IgG antibody responses in people with different clinical presentations of malaria. Results: Liquid chromatography–mass spectrometry revealed 17 proteins contained in the ~65 kDa band, with an apyrase and a peroxidase as the two most abundant proteins. Detection of IgG antibodies against salivary antigens by ELISA revealed a significant higher antibody levels in people with malaria infection when compared to uninfected volunteers using the AnDar_Apy1 and AnDar_Apy2 peptides. We also detected a significant positive correlation between the anti-peptides IgG levels and antibodies against the P. vivax and P. falciparum antigens PvMSP1 and PfMSP1. Odd ratios suggest that people with higher IgG antibodies against the apyrase peptides were up to five times more likely to have a malaria infection. Conclusion: Antibodies against salivary peptides from An. darlingi salivary gland proteins may be used as biomarkers for malaria risk.